Vaginal Delivery in Placental Abruption - Adjie, JM Seno; Ghazali, M Farid; Khusen, Denny (Indonesian Socety of Obstetrics and Gynecology, 2018)
Objective: To describe the case of vaginal delivery in placental abruption.   Methods: A case report   Results: In the case of placental abruption, we could perform vaginal delivery.   Conclusion: The treatment of placental abruption can be vaginally or by cesarean section depending on the severity of disease, gestational age, and state of the mother and fetus. Keywords: IUFD, placental abruption, vaginal delivery